Towards a Fabric-Based Soft Hand Exoskeleton for Various Grasp Taxonomies - Peñas, Andrea; Maldonado-Mejía, Juan C.; Ramos, Orion; Múnera, Marcela; Barria, Patricio; Moazen, Mehran; Wurdemann, Helge; Cifuentes, Carlos A. (My University, 2022)
This paper describes a functional evaluation test of a fabric-based hand exoskeleton for various grasp taxonomies. We conducted an adapted version of the Jebsen Taylor Hand Function Test (JTHFT) with a healthy subject. The evaluation investigates a comparison of the times it takes the user to perform the task with and without the device, establishing a range of actions with a delay of 2.0–6.0 s maximum. This preliminary study aims to understand the implications of future clinical studies with post-stroke patients for rehabilitation.
Keywords: fabric-based exoskeleton; hand rehabilitation; rehabilitation robotics; soft-robotics